A Numerical Study of Linear Long Water Waves over Variable Topographies using a Conformal Mapping - Flamarion, M. V.; Ribeiro-Jr, R. (Trends in Computational and Applied Mathematics, 2022)
In this work we present a numerical study of surface water waves over variable topographies for the linear Euler equations based on a conformal mapping and Fourier transform. We show that in the shallow-water limit the Jacobian of the conformal mapping brings all the topographic effects from the bottom to the free surface. Implementation of the numerical method is illustrated by a MATLAB program. The numerical results are validated by comparing them with exact solutions when the bottom topography is flat, and with theoretical results for an uneven topography.